The Effect of Back Massage on Labor Pain in Phase I Active in Maternity Mothers at PMB Intan In Tangerang District 2022 - Ismarina; Prihayati; Marthia Ikhlasiah; Kurniahawa Arta (Nursing and Health Sciences Journal (NHSJ), 2023)
Background:The most important midwifery care in the delivery process is to apply the principle of "Dear Mother" namely respecting each other's culture, beliefs and desires of the mother and involving the husband and family. Non-pharmacological pain management can be carried out by most health care providers (doctors, nurses and midwives) who may also involve the mother's family, including back massage. Objective: Knowing the effect of back massage on labor pain during the first active phase in labor mothers Method: This research is a type of descriptive research with a quasy experimental research design with pretest posttest one group with the sample of this study namely mothers in the active phase of the first stage of labor who experience labor pain as many as 30 respondents. This sample was taken using a purposive sampling method with a measuring instrument, namely a numerical pain scale, an observation sheet with an ANOVA analysis test. Results: The results of this study show that there are differences in labor pain after back massage. There is a coercive effect between back massage and labor pain with a P value = 0.00 (<0.05), husband's assistance with labor pain with a P value = 0.03 while there is no significant effect between parity and labor pain with a P value = 0.07. Conclusion: There is an effect of back massage on labor pain in the first active phase of the birthing mother. Suggestion: it is hoped that more/frequent back massage techniques are performed to reduce labor pain during the first active phase according to SOP.